Design Research of ATV Axle Housing based on Blind Number Theory and FEA Method - Zhou Junchao; Tian Jianping; Guo Cuixia; Liao Yinghua; Zhang Shengkai; Zhu Junjun (Jixie chuandong)
In order to solve the issues of all- terrain vehicle（ ATV） axle housing design process appears poor design efficiency and timeliness security,a reliability calculation method of certain type of all- terrain vehicle integral type axle housing based on the finite element method combined with the blind number theory is presented,the all- terrain vehicle axle housing design methods in full of uneven road is obtained by taking the integral type axle housing under the condition of the loaded with uneven road,wheels withstand the maximum tangential force,wheels withstand the maximum lateral force,and the axle housing conditions of stress and deformation as restriction. The simulation results show that based on the analysis of the results of finite element analysis,the calculation efficiency of the design of the all terrain vehicle axle housing is improved,combined with the load and the strength of the time- varying characteristics,a simple calculation method for the structure reliability of the all terrain vehicle axle housing by using blind number theory is provided.